Mapping of the fibroblast growth factors in human white adipose tissue. - Mejhert, N; Galitzky, J; Pettersson, A; Bambace, C; Blomqvist, L; Bouloumié, A; Frayn, K; Dahlman, I; Arner, P; Rydén, M (2010)
CONTEXT: Fibroblast growth factors (FGFs) regulate the development of white adipose tissue (WAT). However, the secretion and cellular origin of individual FGFs in WAT as well as the influence of obesity are unknown. OBJECTIVE: Our objective was to map FGFs in human sc WAT, the cellular source, and association with obesity. DESIGN: Secretion, mRNA, and circulatory levels of FGFs in human abdominal sc WAT from nonobese and obese donors were examined by microarray, real-time quantitative PCR, and ELISA. The activity of FGFs in cultured human adipocytes was determined by phosphorylation assays. RESULTS: Expression of five FGFs (FGF1, FGF2, FGF7, FGF9, and FGF18) and FGF homologous factor (FHF2) was identified in WAT. Only FGF1 was released in a time-dependent manner from sc WAT, and fat cells were the major source of FGF1 secretion. FGF1 expression increased and FGF2 decreased during adipocyte differentiation. Furthermore, FGF1 was not secreted into the circulation. Although FGF1 levels were 2-fold increased in obesity, they were unaltered by weight reduction. Only FGF1 and FGF2 induced a marked concentration-dependent phosphorylation of p44/42 in cultured human adipocytes. CONCLUSIONS: Of the investigated FGFs, only FGF1 is secreted from sc WAT and predominantly so from the adipocyte fraction. The activity in adipocyte cultures and lack of secretion into the circulation suggest that FGF1 acts as an auto- or paracrine factor. FGF1 levels are increased in obesity but unaffected by weight reduction, suggesting a primary defect in obese individuals. In conclusion, FGF1 may play a superior role among the FGFs in sc WAT and obesity development.